Study of the impact of herbal medicinal products in soft dosage forms on the burn wound progression in the experiment - Iermolenko, Tamara; Ruda, Natalia; Pautina, Elena (My University, 2019)
The treatment of burns with topical preparations, i.e. with ointments, which consist of herbal ingredients, becomes relevant among the population due to the fact that this dosage form is most convenient to apply as self-medication; and biologically active substances that are part of these preparations are less toxic, and at the same time they are not less effective than synthetic drugs against burn damages.Purpose. To study medicinal effect of the drugs, which contain biologically active herbal ingredients using the model of burn wound.When treating the burn wounds with Wunderhill ointment and 2% thiotriazoline ointment, the wound healing progression was better. The burn wound area for the next two weeks of observation (Days 14-21) decreased faster in comparison with the application of Spasatel Forte ointment and much faster in comparison with the group of pathology. On Day 28 the burn wound was epithelized completely. According to the results of the experiment, the effect of Wunderhill ointment was most pronounced in relation to all the soft dosage forms under study.
Keywords: herbal medicinal products; soft dosage form; burn wound; healing